Mitochondrial carbonic anhydrase (isozyme V) in mouse and rat: cDNA cloning, expression, subcellular localization, processing, and tissue distribution. - Nagao, Y (1994)
When the human cDNA, isolated on the basis of homology to the murine carbonic anhydrase (CA) "Y" was expressed in COS cells, the human CA was targeted to and processed in mitochondria, as expected for CA-V. However, tissue distribution reported for the corresponding mouse CA Y mRNA was much more limited than that reported for the distribution of CA-V immunostaining in rat tissues. To determine whether the murine cDNA actually encodes a mitochondrial CA activity and to compare the tissue distribution of the homologous murine and rat gene products, we used reverse transcription-PCR to reisolate the murine CA-V candidate cDNA and used the murine cDNA probe to isolate the homologous rat cDNA. We compared the two cDNA sequences, the activities they expressed after transfection of COS cells, and the sites of N-terminal processing of expressed products. In addition, we used antibodies to the C-terminal peptides predicted from each cDNA to compare distribution of CA-V in mouse and rat tissues and to identify CA-Vs in mitochondria isolated from mouse and rat liver. From these studies, we conclude that both mouse and rat CA-V candidate cDNAs encode active CAs that are targeted to and processed in mitochondria and that there are real differences in tissue distribution of CA-V between mouse and rat. However, the findings that are M(r) of CA-V in rat tissues is smaller than that previously reported and that the tissue distribution also differs lead us to conclude that the antibody used in prior reports most likely misidentified another antigen in rat tissues as CA-V.